HUBUNGAN PENGETAHUAN DAN SIKAP IBU DENGAN PENCEGAHAN ISPA PADA ANAK BALITA - Sherly Widianti; Desi Indra wati (Jurnal Kesehatan dan Pembangunan, 2026)
Acute Respiratory Infection (ARI) remains a major cause of morbidity among under-five children. Mothers play an important role in preventing ARI through adequate knowledge and positive attitudes. This study aimed to determine the relationship between mothers’ knowledge and attitudes with ARI prevention among under-five children in the working area of Puskesmas Sosial Palembang in 2025. This quantitative study employed a cross-sectional design involving 61 respondents selected using total sampling. Data were collected using questionnaires and analyzed using univariate and Chi-Square tests. The results showed that most respondents had sufficient knowledge (54.10%), negative attitudes (54.10%), and good ARI prevention practices (57.38%). Statistical analysis indicated a significant relationship between knowledge and ARI prevention (p=0.002) and between attitude and ARI prevention (p=0.002). It can be concluded that mothers’ knowledge and attitudes are significantly associated with ARI prevention in under-five children.